2011
DOI: 10.1016/j.ajpath.2011.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Cell Proliferation by Enhanced Mitochondrial Biogenesis via mtTFA in Arsenical Skin Cancers

Abstract: Arsenic-induced Bowen's disease (As-BD), a cutaneous carcinoma in situ, is thought to arise from gene mutation and uncontrolled proliferation. However, how mitochondria regulate the arsenic-induced cell proliferation remains unclear. The aim of this study was to clarify whether arsenic interfered with mitochondrial biogenesis and function, leading to aberrant cell proliferation in As-BD. Skin biopsy samples from patients with As-BD and controls were stained for cytochrome c oxidase (Complex IV), measured for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 41 publications
9
69
0
Order By: Relevance
“…Beside ovarian cancer, TFAM upregulation is also observed in breast, colorectal, bladder, endometrial and arsenic induced skin cancer with subsequent increase in MtBIO and cellular proliferation. Many study show similar results both in experimental and clinical settings [71][72][73][74][75][76][77]. Such findings suggest TFAM as one of the most important therapeutic targets in chemoresistant ovarian cancer.…”
Section: Mitochondrial Transcription Factor a (Tfam)supporting
confidence: 68%
See 1 more Smart Citation
“…Beside ovarian cancer, TFAM upregulation is also observed in breast, colorectal, bladder, endometrial and arsenic induced skin cancer with subsequent increase in MtBIO and cellular proliferation. Many study show similar results both in experimental and clinical settings [71][72][73][74][75][76][77]. Such findings suggest TFAM as one of the most important therapeutic targets in chemoresistant ovarian cancer.…”
Section: Mitochondrial Transcription Factor a (Tfam)supporting
confidence: 68%
“…Upon import to mitochondria it performs multiple regulatory functions including mtDNA transcription, maintenance of mtDNA looping, coating and packaging (mitochondrial nucleoids) [59,69,70]. It contains facets for binding nuclear respiratory factor (NRF) 1 and NRF2 which act on the promoter of D-loop region leading to increased mtDNA copy number [71]. Significant overexpression of TFAM was observed in human serous ovarian cancer in association with poor 5-years survival.…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…To confirm the results for mitochondrial DNA content, we studied the expression of COX6c. This protein is localized on the mitochondrial inner membrane and is considered to be a reliable marker of mitochondrial content (36,37). The COX6c protein is expressed in trophoblastic and mesenchymal cells, with a stronger expression in trophoblastic cells.…”
Section: Mitochondrial Contentmentioning
confidence: 99%
“…In particular, it has been demonstrated that PGC1a may function as a co-activator of androgen receptor thus favoring the proliferation of prostate cancer [13]. In cutaneous carcinoma an increased expression of PGC1a, NRF-1 and TFAM was found pointing to an implication of mitochondrial biogenesis as crucial event in tumor cell growth [15]. In line with its pro-tumour activity, PGC1a loss protects mice from colon and liver carcinogenesis induced by azoxymethane and diethylnitrosamine respectively, by a mechanism involving the inhibition of lipogenesis-stimulated tumor The peroxisome proliferator activated receptor gamma co-activator 1 alpha (PGC1a) is an inducible transcriptional co-activator with direct function in the induction of mitochondrial biogenesis.…”
Section: Introductionmentioning
confidence: 97%